Detection of submicroscopic chromosomal aberrations by array‐based comparative genomic hybridization in fetuses with congenital heart disease. (April 2014) - Yan, Y.; Wu, Q.; Zhang, L.; Wang, X.; Dan, S.; Deng, D.; Sun, L.; Yao, L.; Ma, Y.; Wang, L.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2014; 43: 363–363